Reassessment of Begonia arboreta and B. sonlaensis (Begoniaceae) based on field observation and type examination - Chen, Wen-Hong; Radbouchoom, Sirilak; Nguyen, Hieu Quang; Phutthai, Thamarat; Averyanov, Leonid V.; Shui, Yu-Min (Phytotaxa, 2018)
Due to the unavailability of specimens and publications in the past, some gaps exist in knowledge of similar species from various adjacent countries. After more recently detailed observations from field surveys and examinations on herbaria specimens, we confirmed the status of Begonia arboreta and B. sonlaensis as synonyms of B. garrettii and B. pseudodryadis from China and Thailand, and from China and Vietnam, respectively. The taxonomic treatment is based on the examination of both available herbarium specimens and living plants from different populations. Taxonomy revision of the allied species is very important for understanding plant diversity in the above neighboring countries.